Dampak Earnings Reporting Lags Terhadap Koefisien Respon Laba - Jaswadi Jaswadi (The Indonesian Journal of Accounting Research, 2013)
The objectives of the study are: (1) to analyze the mean difference of market reaction to semi-annual versus annual earnings announcement; (2) to analyze the mean difference of semi-annual versus annual ERC; and (3) to empirically investigate the impact of reporting lags on ERC. This study uses a time-series of 47-listed company on the JSX during 1992-2001. The sample was proportionally selected from 8 industries. This study uses the 10 years time-series on the equation 1 and 10 years pooled-time series on the equation 2. The t test on semi-annual versus annual abnormal return and ERC of equation 1 was used to test the hypotheses 1 and 2. Furthermore, multiple-regression analysis of equation 2 was used to test the hypotheses 3.The result of this study are as follows:(1) the investors respond indifferently of semi-annual and annual earnings announcement, but cumulatively the semi-annual abnormal return is larger relatively to the annual CAR; (2) semi-annual ERC is greater relatively to the annual ERC; (3) there is negative direction of length of reporting lags on the ERC; and (4) based on sensitivity analysis, the determinants of ERC are earnings persistence, earnings predictability, growth opportunity, leverage and industrial effect. The systematic risk and firm size was inconsistent to the previous studies. The reason is probably caused by the structural change bias during 1997-1998 period.The study extent the ERC issues and contribute to BAPEPAM, mainly to the decrees No. 17/PM/2002 that revised the decrees No. 80/PM/1996. This new decrees shorten the reporting lags of semi-annual and annual financial statement to BAPEPAM. Based on the finding that JSX’s investors respond statistically insignificant the signal of early (lately) issuance of financial statements, it (however) supports the BAPEPAM to gradually shorten the new reporting lags regulation. It is suggested to anticipate the global capital market that requires the real-time and more relevance informations.